Combined Interstitial and Intracavitary High-Dose Rate Brachytherapy of Cervical Cancer - Itami, Jun; Murakami, Naoya; Watanabe, Miho; Sekii, Shuhei; Kasamatsu, Takahiro; Kato, Shingo; Hirowatari, Hisako; Ikushima, Hitoshi; Ando, Ken; Ohno, Tatsuya; Okamoto, Hiroyuki; Okuma, Kae; et al. (Frontiers in Oncology, 2022)
High-dose-rate brachytherapy by remote afterloading is now performed under three-dimensional image guidance by CT or MRI. Three-dimensional image-guided brachytherapy in cervical cancer disclosed that the traditional intracavitary brachytherapy by Manchester method cannot deliver an adequate dose to the large tumor with resulting local recurrence. To improve the local control rate, combined interstitial and intracavitary (hybrid) brachytherapy can increase the dose to the large parametrial involvement without increasing the dose to the rectum and bladder. Whether hybrid brachytherapy can be performed safely on a multi-institutional basis remains to be studied. From 2015, phase I/II study of hybrid brachytherapy was launched in Japan, and it was revealed that hybrid brachytherapy can be performed safely and with a high quality of radiation dose distribution in a multi-institutional study. In Japan, the number of patients undergoing hybrid brachytherapy in cervical cancer is rapidly rising. Education and clinical trial are very important to establish hybrid brachytherapy in the management of cervical cancer.